Problems of Teachers and Parents in Implementing Distance Learning During the Covid-19 Pandemic at SDN 102 Makale 5 - Restiany Paiman; Marwati Abd. Malik; Ajat Sudrajat (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study is to find out the problems experienced by teachers and parents in implementing distance learning during the Covid-19 pandemic and the efforts taken by teachers and parents in overcoming the problems of distance learning at SDN 102 Makale 5. The implementation of distance learning is divided into in two methods, namely in-network (online) and offline (out-of-network) methods. This research is a qualitative research carried out using a case study approach with participants including teaching staff (teachers) consisting of representatives of young and old teachers (6 people) as well as representatives of parents of students from high and low economies at SDN 102 Makale 5 ( 6 people). The main instruments in qualitative research are the researchers themselves and there are three tools for gathering information, namely questionnaires, interview guides, and document studies. The subjects in this study were informants, namely people who provided information about the data needed regarding teacher and student perceptions of the impact of online learning during the Covid-19 pandemic at SDN 102 Makale 5. Based on the data collected and analyzed, it was found that teacher problems in carrying out online learning consisted of 4 indicators, namely indicators of learning activities, internet networks, learning resources, and handling learning difficulties with parents. Meanwhile, the problems of parents of students in carrying out distance learning consist of 3 indicators, namely, the readiness of parents in distance learning, the provision of learning facilities and infrastructure, and the handling of student learning difficulties.